People with an intellectual disability in the discourse of chronic and complex conditions: an invisible group? - Goddard, L.; Davidson, Patricia; Daly, J.; Mackey, S. (Australian Healthcare and Hospitals Association, 2008)
People with an intellectual disability and their families experience poorer health care compared with the general population. Living with an intellectual disability is often challenged by coexisting complex and chronic conditions, such as gastrointestinal and respiratory conditions. A literature review was undertaken to document the needs of this vulnerable population, and consultation was undertaken with mothers of children with disabilities and with professionals working within disability services for people with an intellectual disability and their families. Based on this review, there is a need to increase the profile of people with an intellectual disability in the discourse surrounding chronic and complex conditions. Strategies such as guideline and competency development may better prepare health professions to care for people with disabilities and chronic and complex care needs and their families.